Structural view of the 2A protease from human rhinovirus C15. Issue 4 (12th April 2018) - Ling, Hui; Yang, Pan; Hou, Hai; Sun, Yao
Abstract : The 2.6 Å resolution crystal structure of the 2A protease from human rhinovirus C15 (HRV‐C15) reveals the presence of a conserved His–Asp–Cys catalytic triad and a Zn 2+ ‐binding site. Comparison with the structures of 2A proteases from other enteroviruses reveals that the substrate‐binding cleft of the 2A protease from HRV‐C15 shows a more open conformation and is presumably more accessible for substrate binding. Abstract : The majority of outbreaks of the common cold are caused by rhinoviruses. The 2A protease (2A pro ) of human rhinoviruses (HRVs) is known to play important roles in the propagation of the virus and the modulation of host signal pathways to facilitate viral replication. The 2A pro from human rhinovirus C15 (HRV‐C15) has been expressed in Escherichia coli and purified by affinity chromatography, ion‐exchange chromatography and gel‐filtration chromatography. The crystals diffracted to 2.6 Å resolution. The structure was solved by molecular replacement using the structure of 2A pro from coxsackievirus A16 (CVA16) as the search model. The structure contains a conserved His–Asp–Cys catalytic triad and a Zn 2+ ‐binding site. Comparison with other 2A pro structures from enteroviruses reveals that the substrate‐binding cleft of 2A pro from HRV‐C15 exhibits a more open conformation, which presumably favours substrate binding.